2018
DOI: 10.1093/ajcn/nqy132
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo-controlled clinical trial of nicotinamide riboside in obese men: safety, insulin-sensitivity, and lipid-mobilizing effects

Abstract: 12 wk of NR supplementation in doses of 2000 mg/d appears safe, but does not improve insulin sensitivity and whole-body glucose metabolism in obese, insulin-resistant men. This trial was registered at clinicaltrials.gov as NCT02303483.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
246
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 219 publications
(260 citation statements)
references
References 52 publications
13
246
1
Order By: Relevance
“…This supports the lack of effects of NR on insulin resistance and glucose metabolism, as previously reported (Dollerup et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This supports the lack of effects of NR on insulin resistance and glucose metabolism, as previously reported (Dollerup et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Despite the wealth of preclinical data suggesting a medical merit of NR in the treatment of mitochondrial dysfunction, no clinical studies have confirmed these findings in humans. During a double-blinded, placebo-controlled clinical trial in middle-aged, obese and insulin-resistant men (Dollerup et al 2018), skeletal muscle biopsies were collected before and after 12 weeks of NR or placebo supplementation. Here, we aimed to determine if NR supplementation in humans impacts NAD + metabolism and mitochondrial respiration in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation of NR in rodents increases NAD + levels in skeletal muscle (Canto et al 2012), and improves skeletal muscle and muscle stem cell function in mice with aging or muscular dystrophy Zhang et al 2016). The potential effects of NR in human skeletal muscle are unknown, but dietary supplementation of NR in humans increases NAD + and NAD + -related metabolites in plasma, peripheral blood mononuclear cells, and urine Dellinger et al 2017;Dollerup et al 2018;Martens et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…) and one in the American Journal of Clinical Nutrition (Dollerup et al . ), Dollerup and collaborators investigated whether 12 weeks of NRS (2000 mg/day) could improve whole‐body glucose metabolism as well as skeletal muscle mitochondrial respiration and content in obese and insulin‐resistant men. In their papers, Dollerup and colleagues report data indicating that although NRS increases in urinary metabolites of NR (Dollerup et al .…”
mentioning
confidence: 99%
“…In line with these findings, NRS failed to improve insulin sensitivity and glucose tolerance, as assessed using the hyperinsulinaemic–euglycaemic clamp and an oral glucose tolerance test (OGTT), respectively (Dollerup et al . , ). In addition, no effects of NRS were observed on circulating levels of pancreatic hormones (i.e.…”
mentioning
confidence: 99%